Memanfaatkan Limbah Coco Fiber menjadi Produk Ramah Lingkungan Menggunakan Marketing Google My Business - Susanto, Hendra; Muttaqin, Muttaqin; Cahya, Uci Dwi (LPPM Universitas Bumigora, 2024)
Coco fiber is waste that is often produced by society, especially in Langsa area. This is because many Acehnese people use coconut as a cooking ingredient. The aim of this activity is to provide marketing-related training using a digital marketing platform based on Google My Business. The method in this research consists of planning, observation and implementation. The results of the socialization activities have run well and were successful. This activity is proven by the partner's success in creating an account and sending products on that account. To reduce too much coconut fiber waste, it is necessary to have a recycling process for this waste into products with high selling value. Traditionally, coconut fiber is only used to make brooms, doormats, ropes and other household items. The society has utilized coconut fiber waste into an environmentally friendly product that is very beautiful and has high selling value. It has the impact of increasing participants' knowledge and understanding of digital product marketing and increasing their confidence in marketing their products online.